ENHANCING AGRICULTURAL PROGRESS VIA SUSTAINABLE PRODUCTION AND CONSUMPTION - Nistoroiu, Bianca-Florentina; Privitera, Donatella; Prahoveanu, Ștefan Laurențiu; Emek, Mustafa Latif; Condeianu, Ovidiu (Economics of Agriculture, 2024)
The paper’s main aim is to discuss the importance of reducing environmental impact, conserving biodiversity, and addressing socio-economic concerns within the context of agriculture. The research methodology involves a comprehensive review of existing literature, and data analysis to address the following research questions: By emphasizing the interdependence of ecological, social, and economic factors, the paper provides insights into holistic approaches to sustainable agriculture. The paper contributes to the field by offering practical recommendations and policy implications for policymakers, practitioners, and stakeholders involved in agriculture. It highlights the importance of collaborative efforts among various stakeholders to foster innovation, promote knowledge sharing, and drive systemic change towards a more sustainable food system. Through its interdisciplinary approach, the paper bridges gaps in understanding and offers pathways for achieving agricultural progress while safeguarding the environment and ensuring food security for future generations.